PENGEMBANGAN KAPASITAS SUMBER DAYA MANUSIA MELALUI PELATIHAN MANAJEMEN BERBASIS KOMUNITAS - Agus Sobar; Eva Fathussya'adah; Noornissa Sarah Ginanjar (HARUPAT: Jurnal Pengabdian Masyarakat Multidisiplin, 2026)
Human resource (HR) development is a crucial pillar in driving the social and economic progress of society, particularly through participatory approaches at the local level. This article aims to describe the implementation and analyze the impact of a community service program titled “Human Resource Capacity Development through Community-Based Management Training”. The primary problem underlying this activity is the managerial limitations faced by micro-entrepreneurs, such as a low understanding of business planning, financial management, and marketing strategies. The implementation method utilized a participatory and need-based approach, conducted on January 24, 2026, for a community of MSME (Micro, Small, and Medium Enterprises) actors. The stages of the activity included preparation (needs identification), training implementation through interactive classes (lectures, discussions, case studies, and simulations), as well as evaluation and follow up. The results of the activity show a significant increase in participants' knowledge and practical skills, particularly in developing business plans, simple financial recording, and structured decision-making. Furthermore, this training successfully strengthened social capital in the form of cooperation and trust among community members. Despite constraints such as varying levels of participant understanding, this program proved to be an effective community empowerment model capable of enhancing the independence and competitiveness of HR at the local level.